The Effect of Using Board Game on Students’ Speaking Ability - Roswati Roswati; Ame Rahmadawanti (Indonesian Journal of Integrated English Language Teaching, 2016)
The main objectives of this research were to find out whether there is significant difference of students’ speaking ability taught by using and taught without using board game of the eighth grade students at Junior Islamic Boarding School Darel Hikmah Pekanbaru and whether there is significant effect of using board game on students’ speaking ability of the eighth grade students at Junior Islamic Boarding School Darel Hikmah Pekanbaru. The type of this research was quasi-experimental design. The writer used two groups pre-test and post-test design. The writer used experimental and control classes as sample of the research by using cluster random sampling in which the total sample was 40 students chosen from 5 classes as the population of this research. The writer used content validity and inter-rater reliability. In collecting the data, the writer used oral test. While, in analysing the data, the writer used independent sample t-test and effect size. Based on the data analysis, the writer found that t-test calculation is 6.150. It is higher than standard on t-table that is 2.72 in 1% and 2.02 in 5%. It can be read 2.02<6.150>2.72. Therefore, Ho is rejected and Ha is accepted; or there is significant difference of students’ speaking ability taught by using and taught without using board game of the eighth grade students at Junior Islamic Boarding School Darel Hikmah Pekanbaru. It also can be seen from effect size calculation that was calculated by using eta squared formula with the result 0.49 or categorised as large effect. Regarding the result of the effect size above, it can be concluded that there is significant effect of using board game on students’ speaking ability of the eighth grade students at Junior Islamic Boarding School Darel Hikmah Pekanbaru.